Manipulation of epsilon-near-zero wavelength for the optimization of linear and nonlinear absorption by supercritical fluid - Jiaye Wu (Nature Portfolio, 2021)
Abstract We introduce supercritical fluid (SCF) technology to epsilon-near-zero (ENZ) photonics for the first time and experimentally demonstrate the manipulation of the ENZ wavelength for the enhancement of linear and nonlinear optical absorption in ENZ indium tin oxide (ITO) nanolayer. Inspired by the SCF’s applications in repairing defects, reconnecting bonds, introducing dopants, and boosting the performance of microelectronic devices, here, this technique is used to exploit the influence of the electronic properties on optical characteristics. By reducing oxygen vacancies and electron scattering in the SCF oxidation process, the ENZ wavelength is shifted by 23.25 nm, the intrinsic loss is reduced by 20%, and the saturable absorption modulation depth is enhanced by > 30%. The proposed technique offers a time-saving low-temperature technique to optimize the linear and nonlinear absorption performance of plasmonics-based ENZ nanophotonic devices.